(untitled) (Journal of Soft Computing Exploration, 2025)
The integration of information technology plays a vital role in improving organizational performance and supporting sustainable agricultural practices through efficient seed management systems. The existing manual seed ordering and purchasing process at Republik Bibit Nursery has led to several inefficiencies, including inaccurate stock data, transaction errors, and difficulties in estimating seed requirements. This study aims to develop an Information System of Horticultural Seed Ordering at Republik Bibit Nursery using the Laravel framework to digitalize the ordering process and enhance operational efficiency. The primary objective is to streamline order management, enable real-time stock monitoring, track seedling growth, and assist customers in estimating seed quantities based on land size. The novelty of this research lies in the integration of e-commerce functionality with agricultural decision-support features such as growth tracking and stock forecasting—an advancement beyond conventional systems that focus solely on sales transactions. The system was developed using the Waterfall method, encompassing six stages: requirement analysis, design, implementation, testing, deployment, and maintenance. Data collection was conducted through observation, interviews, and literature review to ensure comprehensive system requirements. The implementation resulted in a fully functional web-based application featuring modules for user management, product management, transactions, and reporting. Through Black Box testing, all functional scenarios for different user roles—admin, owner, employee, and customer—achieved a 100% success rate, confirming the reliability of the system. The results demonstrate that this information system effectively minimizes transaction errors, reduces seed stock shortages, and enhances decision-making accuracy for both administrators and customers. In conclusion, the developed system provides an efficient, scalable, and sustainable digital solution that supports the modernization of horticultural nurseries and contributes to the broader digital transformation of the agribusiness sector.